Analysis of Mathematical Creative Thinking Ability after Experiencing Learning of Expansions of Numbers Toward Realistic Mathematics Learning Approach - Erwin; Hongki Julie (Riemann: Research of Mathematics and Mathematics Education, 2025)
This research aims to analyze the mathematical creative thinking ability of grade VIII students after participating in Realistic Mathematics Learning (PMR) approach on the material of Exponential Number at Bruder Junior High School, Pontianak. The research method used was design research. The subjects in this research were VIII grade students at Bruder Junior High School, Pontianak in the 2023/2024 academic year, with the experiment class in VIII-B and the research class in VIII-G. Data collection was done through tests, interviews, and documentation. The instruments used in the data collection process were test sheets, and interview guideline sheets. The instrument and data validation technique used in this research is validation of the supervisor and uses triangulation theory to test the validity of data obtained from the field. The data analysis process in this research is data reduction, data presentation, conclusion drawing. The results of this research are out of 27 students, three students (11%) have high creative thinking skills, 22 students (81.5%) have moderate creative thinking skills, and two students (7.5%) have low creative thinking skills.